12 astounding athletic feats - Bell, Samantha (Bell, Samantha. Incredible., 2020)
Profiles twelve athletes who hold records and have achieved impressive things in their fields--from Florence Griffith Joyner who set the record for world's fastest woman in 1988 that still holds today, to Wilt Chamberlain, who holds the record for scoring 100 points in a single NBA basketball game. Includes a glossary.